Anatomy study of the genus Cirsium Mill. in Iran - Sheidai, Masoud; Shojaei, Saeedeh; Koohdar, Fahimeh (Acta Biologica Szegediensis, 2018)
The genus Cirsium Mill. (Asteraceae) also known as plume thistles with about 250 perennial, biennial or rarely annual spiny species is a phylogenetically unresolved and paraphyletic genus. Cirsium species grow in different ecological conditions and tend to form interspecific hybrids. Some species are morphologically very similar and need to be delineated by additional anatomical and molecular characters. About 28 Cirsium species have been reported in Flora Iranica; they were classified in five sections. Taxonomic investigation of these species was confined to morphology and molecular study of RAPD and ISSR markers. The present study carried out anatomical investigation (leaf and stem characters) of Cirsium species in the country. PCoA analysis of anatomical characters could delimit the studied species and the grouping obtained was almost in agreement with morphological and sectional delineation of the genus. The results obtained are in agreement with several other investigations and all together suggestive of the continued gene flow and introgression between Cirsium species that make taxonomy and phylogenetic relationship of the species difficult.